1991
DOI: 10.1111/j.1365-2141.1991.tb04377.x
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide treatment for chronic graft‐versus‐host disease

Abstract: The treatment of chronic graft-versus-host disease (GVHD) may present a difficult therapeutic problem. We used thalidomide to treat six patients with severe chronic GVHD who failed to respond to standard immunosuppressive agents. Four of the six patients showed a clear response to thalidomide, with the fifth patient showing a partial response. The best results were seen in patients with chronic cutaneous GVHD. Two of the patients developed neurophysiological evidence of a peripheral neuropathy, associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 18 publications
1
33
2
Order By: Relevance
“…In this trial sedation and constipation were the major side-effects and four patients discontinued their medication for peripheral neuropathy. Heney et al 30 who treated six patients with refractory cGVHD reported similar results: four patients had a dramatic response and one a partial response. In two patients peripheral neuropathy was observed.…”
Section: Thalidomide (N-phatalidoglutarimide)supporting
confidence: 64%
“…In this trial sedation and constipation were the major side-effects and four patients discontinued their medication for peripheral neuropathy. Heney et al 30 who treated six patients with refractory cGVHD reported similar results: four patients had a dramatic response and one a partial response. In two patients peripheral neuropathy was observed.…”
Section: Thalidomide (N-phatalidoglutarimide)supporting
confidence: 64%
“…Studies on the pharmacokinetics of thalidomide are not available in the mouse; in a rabbit model, however, treatment of the animals with two or three doses of 150 mg/kg thalidomide improved absorption and accumulation of the drug in the serum (20). Peak serum levels obtained after three injections of 150 mg/kg thalidomide (20) are similar to those obtained in humans treated with thalidomide for graft-versus-host disease (21). In our experiments, the need to use two doses of 200 mg/kg thalidomide to achieve cytokine modulation may reflect the poor solubility and bioavailability of the drug (22).…”
Section: Discussionmentioning
confidence: 64%
“…Main adverse effects were sedation, neuropathy and constipation. 58 Heney et al 61 reported responses in five of six persons receiving thalidomide, 100-200 mg/day. Response was best in skin cGVHD.…”
Section: Imid-class Drugsmentioning
confidence: 99%